SPECIFICS OF DRUG PHARMACOKINETICS IN PREGNANCY - A.V. Ostrovskaya; S.A. Sher (Union of pediatricians of Russia, 2010)
Applying clinical pharmacology guidelines to the mother-fetus system makes it possible to better understand the specifics of pharmacokinetics during pregnancy. The article illustrates the factors that drive these specific features related to both changes in the boy of a future mother and the presence of an extra fetal-placental blood circulation, especially the placenta and developing fetus. These factors influence the results of drug-based treatment during the entire gestational period. Thanks to a rapid development of molecular technologies in the last decade, modern medicine has good prospects of answering questions about individual specifics of pharmacokinetics and metabolism of drugs, increased teratogenic risk driven by specifics of genotypes of the mother and fetus. Key words: pharmacokinetics, drugs, pregnancy, placenta, mother-fetus system. (Pediatric Pharmacology. - 2010; 7(5):44-47)